Healing potential of hybrid materials for structural composites. (April 2015) - Selver, Erdem; Potluri, Prasad; Soutis, Costas; Hogg, Paul
Abstract: The healing potential of light-weight hybrid composites consisting of S-glass and polypropylene fibres in an Araldite LY564 epoxy resin has been investigated. This paper describes a co-mingling process for creating glass–polypropylene hybrid yarns. Cross-ply laminates consisting of hybrid yarns in an epoxy matrix have been tested under low energy impact as well as compression after impact (CAI) loading conditions. The study examines the potential for healing the damage cracks developed during impact, with polypropylene fibres. Key part of this investigation is to evaluate the healing potential of polypropylene fibres through local heating. The study shows that with a simple heat treatment process, significant reduction in the impact induced damage area and a corresponding increase in the compression after impact strength can be achieved; a 65% strength improvement has been measured for the healed specimens when compared to unhealed specimen.